Free convection heat transfer from radial heat sink with wing fins shape: An experimental investigation - Mohamed, Hayder Anwar; Tahseen, Tahseen Ahmad (Edelweiss Applied Science and Technology, 2024)
Although cylindrical heat sinks increase the surface area of heat transfer, they are frequently used as enhancers of heat transfer. Base on free convection heat transfer, fins with novel designs are used to improve thermal heat performance. The current experimental investigation examines the influence of a new-fin shape effect on the thermal behavior of a circular-base radial heat sink. Heat-supplied rates of, 136, 260,375, 589 and 808 W were the subjects of the investigation. Parametric models were used to compare the impacts of fin shape, fin number, and heat flow on the thermal resistance and total heat transfer coefficient. The results show the Nusselt increase with 22% in the 16th fins case and 88% in the 24th fins case compared with ideal case 8th fins, respectively at high input heat rate. In addition, the heat transfer occurred under free convection conditions, which is reason it was discovered that the higher fins number were more efficient in removing heat compared to those with smaller fins.